1995
DOI: 10.1111/j.1365-2044.1995.tb06035.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of the pre‐operative ECG

Abstract: The utilisation of the pre-operative ECG inpatients undergoing routine surgery was investigated in 354 adult patients over a 2-week period. Sixty-four percent of patients had an ECG pre-operatively. An ECG was not performed in 17% of patients who, current hospital policy suggests, should have had one. In contrast, an ECG was performed in 33% ofpatients who, hospital policy suggests, have no need of one (all of which were normal), which represented 18% of the total number of pre-operative ECGs performed.In 62% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
7

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 6 publications
0
11
0
7
Order By: Relevance
“…Studies have looked into the need for the routine ECGs and chest radiographs. [131415] In a large study involving 6111 patients undergoing elective surgery, the usefulness of routine chest radiographs and its influence on anaesthetic management was evaluated. [16] They found 18.3% were abnormal out of which only 5.1% (313 patients) were considered as useful which altered anaesthetic management.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have looked into the need for the routine ECGs and chest radiographs. [131415] In a large study involving 6111 patients undergoing elective surgery, the usefulness of routine chest radiographs and its influence on anaesthetic management was evaluated. [16] They found 18.3% were abnormal out of which only 5.1% (313 patients) were considered as useful which altered anaesthetic management.…”
Section: Discussionmentioning
confidence: 99%
“…Our search identified 30 studies of preoperative electrocardiography, of which 16 reported outcome data in a usable form. 35,37,40,[45][46][47][48]56,57,[59][60][61][62][63][64][65] All were simple case-series. Nine studies were in adults, 37,40,45,46,56,57,60,63,65 two studies in both adults and children, 47,64 and in the remainder of the studies the age of the study population was not specified.…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…Da bei der Planung einer Operation immer mehrere Ärzte beteiligt sind, macht es durchaus Sinn zu überlegen, ob ein standardisiertes Programm für präope-rative Untersuchungen zur Risikominderung beitragen kann. Während es für erwachsene Patienten eine umfangreiche Literatur über die Notwendigkeit von präoperativen Untersuchungen gibt [4, 10, 25, 30, 47-49, 63, 65] [4,6,12,13,15,17,18,20,25,39,43,45,47,49].…”
Section: Methodik Und Ergebnisseunclassified